We Built This City: Public Participation in Land Use Decisions in Singapore. Issue 2 (18th December 2015) - LEE, Jack Tsen-Ta
Abstract: This article considers the extent to which the legal framework for making land use decisions in Singapore allows for public participation. It examines the issue from two angles: the creation and preservation of the built environment, and the transient use of public space. The first angle is discussed primarily from a heritage law viewpoint, focusing on planning law, compulsory acquisition law, and the legal regime for creating national monuments. As for the second angle, the article looks at how the use of common spaces for assemblies and processions is regulated. The foregoing are examined in the context of Edward Soja's assertion in Seeking Spatial Justice (2010) that the equitable distribution of resources, services, and access in cities is an important right.